Getting people to experience it: a grounded theory of the process of integrating a First Nations wellbeing program within university curricula - Orih, Dominic; Cheer, Karen; Morgan, Rhian; Udah, Hyacinth; Tsey, Komla (Frontiers in Education, 2025)
BackgroundThe wellbeing of university students is crucial for their success. Yet educators struggle with the lack of frameworks to integrate wellbeing into core curricula, and universities often relegate wellbeing initiatives to extracurricular activities. These initiatives frequently fail to engage students and the potential impact to wellbeing is reduced. In Australia, universities are also encouraged to integrate First Nations Knowledge within mainstream curricula, but some academics may be skeptical about the relevance of these knowledge systems in specific disciplinary settings. This study addresses these challenges by exploring the integration of the First Nations-developed Family Wellbeing (FWB) program—a wellbeing-focused soft skills approach—into core university curricula.MethodsUsing constructivist grounded theory methodology, the authors developed the theoretical model “Getting people to experience it,” drawing on in-depth interviews with eight educators who integrated the FWB program within core university curricula in Australia and internationally.FindingsThe study examined the challenges, opportunities, strategies, and outcomes of this integration, revealing significant improvements in wellbeing and soft skills for both students and educators. Viewed through the lens of cultural interface, the findings offer valuable insights into bridging First Nations and Western knowledge systems in higher education.ConclusionThe theoretical model provides a practical framework for educators to integrate wellbeing and soft skills as core elements of curricula, rather than treating them as optional add-ons. This work has profound implications for addressing student mental health, enhancing soft skills, and creating a more inclusive and effective educational experience.